Role of polymers and nano materials in enhancing Engineering properties of cement concrete - MOHAN KANTHARIA; PANKAJ KUMAR MISHRA (International Journal of Pharma and Bio Sciences, 2017)
Cement concrete is the only material which has been used maximum for construction of buildings. Now the construction technology is accommodating new materials day by day, Inclusion of polymers and nano materials in cement concrete is getting more attention. Polymers and nano materials are improving the engineering properties of the cement and concrete. Newer kinds of cement concrete composites have more compressive and flexural strength along with improved as chemical resistance, impact resistance and temperature resistance. The polymers which have been commonly used are styrene butadiene rubber, polyvinyl acetate. Acrylic polymers and epoxy polymers have been tested for aggressive exposure such as, for high temperature, chemicals exposures etc. with promising results. Nano materials such as ZnO, nano TiO2, nano ZrO2, nano Al2O3, nano CaCO3have also shown improved water resistance, flexural strength, compressive strength and in reducing cement cracks.This article presents an analytical review of enhancement of mechanical properties ; such as compressive strength and tensile strength,due to addition of polymers and nano composites with cement mortar and concrete.